Al-Furqān Fī Tafsīri Al-Qur’ān Karya Syeikh Ahmad Hassan 1963 M - Ifrohul Fadhilah; Afifatun Nisa Hasibuan; Imam Kurniawan Nst; Muhammad Helmi Ridho (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
An intellectual in the field of contemporary modern century interpretation in Indonesia, Ahmad Hassan with his work Tafsir Al-Furqan. In Indonesia, he is highly respected for his important role in the development of Qur'anic interpretation. Apart from being involved in the world of interpretation, he is also a politician and a reformer in Indonesia. It can be seen from some of his works that tell about politics or other religions. In this study, the author uses a qualitative method that is always used in the approach of library research. In writing his tafsir work entitled Al-Furqan fi Tafsiri Al-Qur'an, he expressed all his anxiety and anxiety about the condition of the Indonesian nation which is still in chaos. His work is very famous until now, even becoming history in the interpretation of the Qur'an in Indonesia.